(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
In this paper, the shear and flexural behavior of reinforced concrete columns corbels having transverse openings is experimentally investigated. Nine standard concrete corbels were subjected to vertical loads in two groups (A and B). Multiple variables were tested in the experimental program, such as the size, shape, location of the openings, and shear span (a/d), as well as the presence or absence of horizontal reinforcement. According to experimental findings, transvers openings have a considerable impact on corbel structural behavior, including characteristics such as ultimate strength, deflection, and failure mechanisms. The technique decreased the ultimate load by 37.9%, the cracking load by (43.75%), the crack width by 100%, and the deflection by 351.6%.